LC50-48 hours and pH tolerance to seeds Kurumoi Rainbow Fish (Melanotaenia parva) - Tutik Kadarini (Jurnal Perikanan dan Kelautan, 2018)
The value of pH concentration on water quality influences the resistance or survival of kurumoi rainbow fish (Melanotaenia parva). Rainbow fish in habitat (natural) live in a pH range of 6.8-8.5 and in cultivation activities the pH range is unknown. At a concentration of pH <7 including acid pH and > 7 including a moderate pH 7 neutral pH. The direct effect of pH will affect water balance as a fish medium and will die when the pH changes extreme or changes rapidly. The aim of the study was to determine the Lethal Concentration (LC5048 hours) and Tolerance both at acidic and basic pH. The test fish used were Kurumoi rainbow fish with a total length of 2.1 ± 0.25 cm and a weight of 0.10 ± 0.05 g of ± 450 tails. There are two experiments, namely the toxicity test of LC50-48 acid pH and toxicity test of LC50-48 alkaline pH. For toxicity tests LC50-48 acid pH consisted of 7 treatments and three replications at different pH levels, namely A) pH 6.0 (control); B) pH 3.50; C) pH 3.96; D) pH 4.48; E) pH 5.07; F) pH 5.74; and G) pH 6.50. Whereas the toxicity test of LC50-48 alkaline pH consisted of 7 treatments and three replications, namely A) pH 7.0 (control); B) pH 8.5; C) pH 9.2; D) pH 9.9; E) pH 10.7; F) pH 11.6 and G) pH 12.5. The parameters observed during the study were ecording dead fish at hours to (0; 24; 48; 72 and 96) and toxicity of LC50-48. The results showed that the toxicity of LC50-48 pH to Kurumoi rainbow fish was at acidic pH of 4.70 and tolerance ranged from 5.07 to 6.50 for 96 hours while alkaline pH was 10.7 and tolerance ranged from 8.5 to 9.9 for 96 hours.